2012
DOI: 10.3109/03009742.2012.697916
|View full text |Cite
|
Sign up to set email alerts
|

Functional limitations and physical symptoms of individuals with chronic pain

Abstract: Chronic pain is a prevalent condition and those who report chronic pain generally suffer from ill health and limitations in their daily life compared to individuals not suffering from the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 49 publications
0
46
0
3
Order By: Relevance
“…First, consistent findings point to socioeconomic indicators, such as educational level, as strong predictors of musculoskeletal disorders and reporting of chronic pain conditions in both men and women [30][34]. MacFarlaine et al found that low socioeconomic status in adulthood was associated with major regional musculoskeletal pain and chronic widespread pain [32].…”
Section: Discussionmentioning
confidence: 97%
“…First, consistent findings point to socioeconomic indicators, such as educational level, as strong predictors of musculoskeletal disorders and reporting of chronic pain conditions in both men and women [30][34]. MacFarlaine et al found that low socioeconomic status in adulthood was associated with major regional musculoskeletal pain and chronic widespread pain [32].…”
Section: Discussionmentioning
confidence: 97%
“…Especially when measuring hand strength and NME, biological sex has been shown to be important to consider when interpreting the results. 27,28 Women with chronic pain also tend to give up physical activity to a greater extent than men, 45 which can further influence the physical measures. To be able to compare these patient groups with healthy volunteers and to limit the effect of different levels of representation, hand strength and NME were stratified by biological sex in the analysis.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Musculoskeletal pain often results in functional limitations in daily life (Bingefors and Isacson, 2004;Bj€ ornsd ottir et al, 2013) and many patients with persistent pain experience a high level of disability, affecting work capacity (Gureje et al, 2001;Gerdle et al, 2004;Landmark et al, 2013). Persistent pain has also been found to negatively influence quality of life (Kroenke et al, 2013;Landmark, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%